2018
DOI: 10.2147/ijgm.s159364
|View full text |Cite
|
Sign up to set email alerts
|

Fever of unknown origin following parathyroidectomy prior to onset of typical polymyalgia rheumatica symptoms: a case report

Abstract: Polymyalgia rheumatica (PMR) is a disease commonly seen in elderly individuals, however, the etiology has not been reported. Typical clinical features include bilateral shoulder pain and morning stiffness, while serologic autoantibody test findings are negative. Approximately 40%–50% of affected patients present with low-grade fever, fatigue, and appetite loss, which we often experience in the field of general medicine, and thus, the condition should not be given low priority. However, knowledge regarding such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Indeed, in these patients, fever is thought to be caused by some cytokines, most notably interleukin-6 and interleukin-1 (IL-6 and IL-1), strongly associated with a CRP increase. On the other hand, fever may itself induce a CRP increase [ 23 , 24 ]. The Belgian researchers suggested that a long delay to a PMR diagnosis might explain this discrepancy possibly caused by laboratory alterations (among these, anemia of chronic disease type) that can influence only ESR [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in these patients, fever is thought to be caused by some cytokines, most notably interleukin-6 and interleukin-1 (IL-6 and IL-1), strongly associated with a CRP increase. On the other hand, fever may itself induce a CRP increase [ 23 , 24 ]. The Belgian researchers suggested that a long delay to a PMR diagnosis might explain this discrepancy possibly caused by laboratory alterations (among these, anemia of chronic disease type) that can influence only ESR [ 22 ].…”
Section: Introductionmentioning
confidence: 99%